The Impact of Digital Solutions on Sustainable Mobility and Traffic Safety in Slovenian Minucipalities - Smole, Tonja; Marič, Miha (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
The chapter discusses the impact of digital solutions on sustainable mobility and traffic safety in Slovenian municipalities, with a special emphasis on the role of real-time traffic data in decision-making support. The purpose of the work is to investigate how digital solutions contribute to the design and implementation of Municipal Integrated Transport Strategies (OCPS) and what obstacles and opportunities the selected municipalities observe in their use. The research is based on a case study of the company Intermatic d.o.o. and on interviews with public administration stakeholders and the company director. Methodologically, it relies on qualitative content analysis, supplemented by analysis of secondary sources. The main findings show that many Slovenian municipalities are already using a variety of digital solutions and that the demand for them is increasing. The key obstacles to a greater level of implementation are the limited human, financial and organizational capabilities of municipalities, and the use of data is hampered by an unsatisfactory level of interoperability. The discussion emphasizes the importance of a well-considered digital transformation without neglecting the human aspect. Among the recommendations, the establishment of uniform national standards in the field of traffic data and a regional approach to traffic management stand out.